2020
DOI: 10.1111/obes.12354
|View full text |Cite
|
Sign up to set email alerts
|

Europe Through the Crisis: Discretionary Policy Changes and Automatic Stabilizers

Abstract: Tax‐benefit policies affect changes in household incomes through two main channels: discretionary policy changes and automatic stabilizers. We study their role in the EU countries in 2007–14 using an extended decomposition approach. Our results show that the two policy actions often reduced rather than increased inequality of net incomes, and so helped offset the inequality‐increasing impact of growing disparities in gross market incomes. While inequality reductions were achieved mainly through benefits using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 50 publications
1
49
0
Order By: Relevance
“…Our results for the overall impact on poverty and inequality of policy changes are also consistent with the existing evidence for some of these countries and/or the crisis period: e.g. for the UK: Adam and Browne, ; Bargain et al , , for Belgium: Decoster et al, , for EU countries during the crisis: De Agostini et al , ; Paulus and Tasseva, .…”
Section: Resultssupporting
confidence: 90%
“…Our results for the overall impact on poverty and inequality of policy changes are also consistent with the existing evidence for some of these countries and/or the crisis period: e.g. for the UK: Adam and Browne, ; Bargain et al , , for Belgium: Decoster et al, , for EU countries during the crisis: De Agostini et al , ; Paulus and Tasseva, .…”
Section: Resultssupporting
confidence: 90%
“…The ability of European tax-benefit systems to stabilise income has been studied by Dolls et al (2012) who found that stabilisation of disposable incomes ranged from 25 per cent to 56 per cent of the overall change in market incomes. Stabilisation of income inequality has also been studied and found to differ substantially from stabilisation of income (Callan et al 2018;Paulus and Tasseva 2018). In this section, we consider the inequality stabilization and redistributive capabilities of each of the tax-benefit systems in the EU-27.…”
Section: The Stabilizing Capability Of European Tax-benefit Systemsmentioning
confidence: 99%
“…Furthermore, means-tested benefits have been shown to be effective in providing a much-needed safety net for households during economic downturns (Bitler et al 2017;Bitler and Hoynes 2016). Recent analysis has also highlighted the importance of tax and benefit automatic stabilisers for income redistribution (Paulus and Tasseva 2020).…”
Section: Introductionmentioning
confidence: 99%